If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 4 = 44 + 2x Reorder the terms: 4 + -2x = 44 + 2x Solving 4 + -2x = 44 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 4 + -2x + -2x = 44 + 2x + -2x Combine like terms: -2x + -2x = -4x 4 + -4x = 44 + 2x + -2x Combine like terms: 2x + -2x = 0 4 + -4x = 44 + 0 4 + -4x = 44 Add '-4' to each side of the equation. 4 + -4 + -4x = 44 + -4 Combine like terms: 4 + -4 = 0 0 + -4x = 44 + -4 -4x = 44 + -4 Combine like terms: 44 + -4 = 40 -4x = 40 Divide each side by '-4'. x = -10 Simplifying x = -10
| 5(4+q)+2q=-22 | | x^2-5x-10000000=0 | | 79=(3x-5) | | -13a+97=188 | | C(x)=500x+100000 | | -2x+2+7x=42 | | 2=-7v-3 | | 100=39+19x | | -3=6z-3z+6 | | 6g-2h=-4 | | 16=8(f+26) | | 61=x-7x+7 | | 4y-8y+6=26 | | -2x-3-3x=-33 | | (x-3-3i)*(x-3+3i)= | | 0=x^2+4x+12 | | x^2+7x=68.75 | | 5x+2y+2=11+9y-x | | 13-ln(5-x)=0 | | 7=5v-19 | | -54=7x+3x+6 | | 2x-4=(2x-9)/2 | | -12=-6j | | 2g-11(-2)=26 | | 0=-6x-2x-8 | | Dy=Cx | | 4/3t=5/2 | | -6x-9+2x=39 | | (3t^2-t-4)(4t^2+3t-1)= | | 2x+5+3x=-25 | | 3(13+5.5k)=6k+18 | | 33=-4x-3x-2 |